До питання нормативно-правового регулювання судово-експертного дослідження рухомих археологічних предметів (артефактів) - Силенок, К.П. (Археологія і давня історія України, 2022)
У статті розглядаються питання нормативно-правового регулювання дослідження рухомих археологічних предметів (артефактів). Звертається увага на законодавство з охорони і збереження археологічної, культурної спадщини, порядку обігу культурних цінностей в Україні. Основна увага приділяється закріпленню поняття рухомих археологічних предметів у законодавстві України та деяких зарубіжних країн. Підіймається також і питання розроблення цієї тематики в законодавстві та в судовій експертизі. Over the centuries, archaeological heritage of Ukraine has been developing under the influence of many factors. Research on such antiquities is a significant task of science for a detailed study of our history, deeper understanding of all stages of the formation, development and promotion of modern culture. Issues arising while protecting archaeological sites are relevant not only for Ukraine but also for many countries of the world. Preservation of history is the important task of every civilised country. Each monument is the source of information, and artefacts of a certain period in their totality represent a holistic cultural layer of history of people who lived in Ukraine no matter whether they were our ancestors or not. The paper outlines the issues of legal regulation of the research of movable archaeological objects (artefacts). Attention is drawn to the legislation on protection and preservation of archaeological and cultural heritage, procedure of cultural properties circulation in Ukraine. The main focus is on enshrining the concept of movable archaeological objects in legislation of Ukraine and some foreign countries. The issue of elaboration of this topic in the legislation and in forensic science is also addressed. Movable archaeological objects are exchanged and traded, such as Palaeolithic art, Bronze Age ornaments, stone axes, etc. Since they can be subject of crimes, and accordingly, can be investigated in forensic institutions, it is required to create a methodology for investigation of movable archaeological objects (artefacts) and conduct systematic research activities for the needs of forensic experts to ensure efficient provision of justice in Ukraine. It is also emphasised that while forensic examination of movable archaeological objects it is vital to establish their authenticity or nonauthenticity.